Berberine represses human gastric cancer cell growth in vitro and in vivo by inducing cytostatic autophagy via inhibition of MAPK/mTOR/p70S6K and Akt signaling pathways - Zhang, Qiang; Wang, Xiaobing; Cao, Shijie; Sun, Yujie; He, Xinya; Jiang, Benke; Yu, Yaqin; Duan, Jingshi; Qiu, Feng; Kang, Ning (Biomedicine & pharmacotherapy, 2020)
[Display omitted] •Berberine represses human gastric cancer cell growth in vitro and in vivo without toxicity to Human peripheral blood mononuclear cells and nude mice.•Berberine induces cytostatic autophagy in BGC-823 cells via inhibition of MAPK/mTOR/p70S6K and Akt signaling pathways.•Autophagy exerts a negative feedback on mTOR/p70S6K, Akt and MAPK signaling in berberine induced cell death. Berberine, an isoquinoline alkaloid from Coptidis Rhizoma, has been characterized as a potential anticancer drug due to its good anti-tumor effects. However, the molecular mechanisms involved in anti-gastric cancer remain poorly understood. Herein, the role of berberine in gastric cancer suppression by inducing cytostatic autophagy in vitro and in vivo was first investigated. Results showed that berberine induced an obvious growth inhibitory effect on gastric cancer BGC-823 cells without toxicity to human peripheral blood mononuclear cells. Treatment with berberine triggered cell autophagy, as demonstrated by the punctuate distribution of monodansylcadaverine staining and GFP-LC3, as well as the LC3-II, Beclin-1 and p-ULK1 promotion, and p62 degradation. Inhibition of autophagy by 3-MA, CQ, Baf-A1 and BECN1 siRNA obviously increased cell viability of berberine-exposed gastric cancer cells, which confirmed the anti-cancer role of autophagy induced by berberine. Mechanistic studies showed that berberine inhibited mTOR, Akt and MAPK (ERK, JNK and p38) pathways thereby inducing autophagy. Inhibition of above pathways increases berberine induced autophagy and cytotoxicity. Interestingly, mTOR/p70S6K was inhibited by the MAPK but not Akt. Furthermore, inhibition of autophagy reversed berberine down-regulated mTOR, Akt and MAPK. In xenografts, the berberine induced autophagy leads to suppression of tumor proliferation with no side-effect, and western blotting displayed an apparent attenuation of p-mTOR, p-p70S6K, p-Akt, p-ERK, p-JNK and p-p38 in tumors from berberine treated mice. Briefly, these results indicated that berberine repressed human gastric cancer cell growth in vitro and in vivo by inducing cytostatic autophagy via inhibition of MAPK/mTOR/p70S6K and Akt, and provided a molecular basis for the treatment of gastric cancer.